2002
DOI: 10.1021/la026216r
|View full text |Cite
|
Sign up to set email alerts
|

Thin Films of Collagen Affect Smooth Muscle Cell Morphology

Abstract: Thin films of the extracellular matrix protein, collagen, were prepared by adsorbing native or heatdenatured type I collagen onto hexadecanethiol self-assembled monolayers. The resulting films were characterized by atomic force microscopy, ellipsometry, and light microscopy. Denatured collagen formed a topographically smooth ∼3.6 nm thick film, consistent with an adsorbed protein monolayer. In contrast, the native collagen thin film consisted of supramolecular collagen fibrils. The density of the large fibrils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
163
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(182 citation statements)
references
References 36 publications
17
163
1
1
Order By: Relevance
“…9 1-Hexadecanethiol ͑Aldrich, St. Louis MO͒, as a 0.5 mM solution in 99.5% ethanol ͑Aldrich͒, was allowed to adsorb to gold films by incubating gold surfaces directly in the thiol solution for 16 h. These substrates were rinsed with ethanol and dried with 0.02 m pore size filtered N 2 prior to incubation with collagen solution.…”
Section: A Alkanethiolate Monolayer Filmsmentioning
confidence: 99%
See 3 more Smart Citations
“…9 1-Hexadecanethiol ͑Aldrich, St. Louis MO͒, as a 0.5 mM solution in 99.5% ethanol ͑Aldrich͒, was allowed to adsorb to gold films by incubating gold surfaces directly in the thiol solution for 16 h. These substrates were rinsed with ethanol and dried with 0.02 m pore size filtered N 2 prior to incubation with collagen solution.…”
Section: A Alkanethiolate Monolayer Filmsmentioning
confidence: 99%
“…9 Phase microscopy images were collected through a 20ϫ objective on a Zeiss Axiovert 100 inverted microscope. Collagen-coated gold coverslip or polystyrene was rinsed with ultra-purified H 2 O ͑Millipore, Billerica, MA͒ and dried with filtered N 2 .…”
Section: Atomic Force Microscopy "Afm… and Phase Imaging Of Substrmentioning
confidence: 99%
See 2 more Smart Citations
“…These controllable patterned structures of collagen were verified to be good scaffolds for cell or soft/hard tissue culture. [10][11][12][13] Some of the works have demonstrated that the supramolecular organization of collagen layers has a strong effect on the behavior of cells, 6,14 showing their potential applications in tissue engineering region. However, the biomineralization inductivity of collagen was not studied although their arrangement and assembly state were said to relate directly to the bone regeneration in vivo.…”
Section: Introductionmentioning
confidence: 99%